Encyclopedia of social psychology - Baumeister, Roy F.; Vohs, Kathleen D. (Gale virtual reference library, 2007)
Includes numerous entries chosen by a diverse team of experts to comprise an exhaustive list of the most important concepts in social psychology. Entries provide brief, clear explanations to the vast number of ideas and concepts that make up the intellectual and scientific content in the area of social psychology.